Calibração de sensores de capacitância (FDR) para estimativa da umidade em diferentes solos - Pizetta, Samuel Cola (2015)
Measurement of soil water content is one of the main challenges of agriculture and knowledge of available equipment to perform it is extremely important. This research aimed to calibrate capacitance sensors (FDR) such as 10HS manufactured by Decagon Devices and two low cost sensors referred to as Grove and Eletrodex. The calibration was carried out through comparisons to soil water content determined by dry oven at 105 o C for three soil classes designated as dystrophic Red Argisol, dystroferric Red Latosol and eutroferric Red Nitosol. For 10HS sensor, the obtained values were compared to calibration curve supplied by the manufacturer. The experiment was set at the Hydraulics Laboratory at Federal University of Lavras, Minas Gerais State in Brazil. It can be concluded that the calibration curve supplied by Decagon Devices did not describe well the results obtained, although this sensor can be satisfactorily used to measure soil water content. According to determination coefficients calculated, low cost sensors did not estimate properly the soil water content at the moisture range evaluated at any soil class.